Effect of the Incorporation of Liposomes Loaded with Rutin on the Transport Properties of Edible Film Produced with Hydroxypropyl Methylcellulose: An in Vitro Release Study - Osorio-Lira, F; Zamorano-Riquelme, M; Silva-Weiss, A (Academic Press, 2024)
This work studied the effect of encapsulating rutin in liposomes on the transport properties of the edible film (EF) produced with hydroxypropyl methylcellulose (HPMC). Encapsulated rutin in liposomes were 106.1 ± 1.2 nm and there was high percentage of encapsulation (89.3 ± 0.5%). When incorporated into the HPMC matrix, the formulation did not show phase separation or agglomeration. Interestingly, the presence of the liposomes caused significant changes in the EF, modifying thickness, yellowness index, and mechanical properties. Less rigid and more deformable EF were obtained with the addition of liposomes and glycerol. The encapsulation of rutin in liposomes, loaded in the EF showed a delay in the liberation of the active compound when compared to non-encapsulated rutin; diffusion coefficients of 3.27*10−16 m2/s and 1.24*10−15 m2/s, respectively. In summary, the presence of liposomes loaded with rutin allows for the production of EF with improved physical characteristics desirable for food systems. Liposomes loaded with active compounds are a good ingredient/carrier for inclusion in EF providing a gradual release of antioxidant agents, with the added benefit of potentially providing a longer shelf life of the food. © 2023 The Authors